PERSEPSI MASYARAKAT TERHADAP PROGRAM ELIMINASI FILARIASIS MELALUI (POMP) SEBAGAI UPAYA PENCEGAHAN FILARIASIS DI KECAMATAN BONANG, KABUPATEN DEMAK - Nur Sulistyaningsih; Syamsulhadi Budi Musthofa; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
The filariasis elimination program through (POMP) is the provision of medicine to all residents in filariasis-endemic areas with DEC, Albendazole and Paracetamol in dosage, annually for at least 5 consecutive years. This research is addressed to the people in Bonang District, Demak Regency, especially Margolinduk and Wonosari villages. This study aims to describe people's perception of filariasis elimination program through (POMP) as filariasis prevention effort in Bonang Sub-district, Demak District. This research is descriptive research with the quantitative method. Respondents in this study amounted to 95. Data collection was done through questionnaire interview and observation. Data analysis is done univariate.The results of this study indicate that the respondents are in the old category of 35 or more than 35 years (52.6%), the primary level of education is less than junior high school (77.9%) and work as housewives (71.4%). Respondents had income below UMR (Rp 1.900.000,00) (66.3%). Some respondents have good knowledge about filariasis elimination program through (POMP) (54,7%), perceived susceptibility (66,3%), perceived severity (74,7%), perceived benefit (67,4%), perceived Barrier (60.0%), and self-efficacy (48.4%). In the implementation of filariasis elimination program through (POMP), there is a need to increase public awareness of the importance of filariasis elimination program through (POMP) as filariasis prevention efforts.